Help! – you need your hands: Contribution of arm movements on balance performance in healthy individuals: A systematic review with meta-analysis - Katharina Borgmann; Thomas Muehlbauer; Mathew W. Hill (PLoS ONE, 2025)
Background Emerging evidence highlights that arm movements exert a substantial and functionally relevant contribution on postural control in healthy individuals. However, performance differences between free versus restricted arm movement for different balance categories with varying levels of task difficulty have not been systematically investigated yet. Objective The objective of this systematic review and meta-analysis was to characterise, aggregate, and quantify performance discrepancies between free and restricted arm movement conditions for diverging balance categories with varying levels of task difficulty in healthy individuals. Methods A systematic search of the literature according to the PRISMA guidelines was performed on the electronic databases PubMed, Web of Science, and SPORTDiscus from their inception date till 1st September 2024. To be applicable for analysis, studies had to report at least one measure of balance performance in healthy individuals. The included studies were coded according to the following criteria: age, sex, status, arm movement conditions, balance test, and test modality. Methodological study quality was assessed using the Appraisal tool for Cross-Sectional Studies. Weighted standardized mean differences (SMD) were calculated and classified according to their magnitude. Results The literature search identified a total of N = 941 records, 25 of which met the inclusion criteria and were analysed in this review. A total of 725 participants (n = 331 females) participated in the studies. The free use of arm movement resulted in moderate (static: SMD = 0.51, dynamic: SMD = 0.66, proactive: SMD = 0.52, reactive: SMD = 0.50) improvements of balance performance. In addition, the performance enhancements were more pronounced for balance tasks with a high (static: SMD = 0.89, dynamic: SMD = 1.04) compared to a low (static: SMD = 0.20, dynamic: SMD = 0.76) difficulty level. Due to a lack of studies, no analysis for measures of proactive and reactive balance was performed. Conclusions The findings revealed that the free use of arm movement positively affects several measures of balance performance, and this is effect is more pronounced for balance tasks with a high difficulty level.